Evaluation of increased fiber, decreased amino acids, or decreased electrolyte balance as dietary approaches to slow finishing pig growth rates. (20th May 2021) - Helm, Emma T; Patience, John F; Romoser, Matthew R; Johnson, Colin D; Ross, Jason W; Gabler, Nicholas K
Abstract: In swine production, pig movement restrictions or packing plant closures may create the need to slow growth rates of finishing pigs to ensure they remain at a marketable body weight when packing plant access is restored. Although dietary formulations can be successful at slowing pig growth, precision is needed regarding how to best formulate diets to achieve growth rate reductions. Thus, the objective was to evaluate three dietary experimental approaches aimed at slowing growth rates in finishing pigs. These approaches consisted of either increasing neutral detergent fiber (NDF), reducing essential amino acids, or reducing the dietary electrolyte balance through the addition of acidogenic salts. A total of 94 mixed-sex pigs (72.4 ± 11.2 kg BW) across two replicates were individually penned and assigned to 1 of 8 dietary treatments ( n = 11–12 pigs/treatment): 1) Control diet representative of a typical corn–soybean meal-based finisher diet (CON); 2) diet containing 15% NDF from soybean hulls (15% NDF); 3) diet containing 20% NDF from soybean hulls (20% NDF); 4) diet containing 25% NDF from soybean hulls (25% NDF); 5) diet formulated as per CON but with 50% of the soybean meal replaced with corn (89% Corn); 6) diet containing 97% corn and no soybean meal or synthetic amino acids (97% Corn); 7) diet containing 2% anhydrous calcium chloride (2% CaCl2 ); and 8) diet containing 4% anhydrous calcium chloride (4% CaCl2 ). Over 28 d, pig body weights and performance were recorded weekly. At d 28, all pigs were ultrasound scanned and switched to the CON diet to evaluate compensatory gain from d 28 to 35. Overall, increased NDF did not impact any growth performance parameter ( P > 0.05). Amino acid restriction reduced average daily gain (ADG), average daily feed intake (ADFI), and gain:feed (G:F) linearly (linear P < 0.001). Similarly, ADG, ADFI, and G:F were linearly reduced with increased CaCl2 inclusion (linear P < 0.001). ADG differed during the compensatory gain period ( P < 0.001), with 4% CaCl2 -fed pigs having a 47% increase in ADG compared with CON-fed pigs. Conversely, 15% and 25% NDF-fed pigs had reduced ADG compared with CON-fed pigs during the compensatory gain period. Gain efficiency differed from day 28 to 35 ( P < 0.001), with 4% CaCl2 -fed pigs having a 36% increase in G:F compared with CON-fed pigs. Altogether, these data demonstrate that both amino acid restriction and CaCl2 inclusion are effective at slowing pig growth, albeit at greater inclusion rates.